EKSPLORASI ETNOMATEMATIKA BATIK MLATIHARJAN DEMAK TERHADAP KONSEP MATEMATIKA GEOMETRI BANGUN DATAR SEKOLAH DASAR - Ida Nur Aini; Sri Wulandari; Eka Zuliana (Universitas Muhammadiyah Makassar, 2023)
Mathematics with cultural nuances is often found in batik. Batik Mlatiharjan is a center for making Demak typical batik which is located in the village of Mlatiharjo, Gajah District, Demak Regency. There are two types of Mlatiharjan batik, namely written batik and stamped batik. Mlatiharjan batik has become part of Demak culture. Researchers can relate the Mlatiharjan batik with the geometric concept of a flat shape. This study used an exploratory qualitative descriptive ethnographic methodology. The ethnomathematics elements in the various motifs of Mlatiharjan batik are the objects of this research. Mrs. Kusmidarmini, the owner of a batik center, is a cultural expert as the subject of this study. Exploration, observation, interviews, and documentation are part of the data collection method. The aim of the Mlatiharjan batik research is to determine the mathematical and philosophical values of the Mlatiharjan batik motifs. The results of this study indicate that each motif has a philosophical meaning and a geometric geometric concept. The motifs include the Guava Flower Motif, Sidomukti Mosque Bledeg, Champa Plate, Demak Great Mosque, Red Guava, Guava Tree, Belimbing Guava, Fish Coral, Demak Crown, and Sidomukti Jambu Bulus Motif. Mathematical concepts that have been found in the variety of batik motifs from Demak, namely geometric shapes such as circles, squares, rectangles, triangles, rhombuses, and trapezoids. In addition, the Mlatiharjan Batik motifs also contain philosophical values related to the life of the Demak people.Matematika yang bernuansa budaya sering ditemukan pada batik. Batik Mlatiharjan merupakan sentra pembuatan batik khas Demak terletak di Desa Mlatiharjo, Kecamatan Gajah, Kabupaten Demak. Terdapat dua jenis batik Mlatiharjan, yaitu batik tulis dan batik cap. Batik mlatiharjan sudah menjadi bagian dari budaya Demak. Peneliti dapat mengaitkan batik Mlatiharjan dengan konsep geometri bangun datar. Penelitian ini menggunakan metodologi etnografi deskriptif kualitatif bersifat eksplorasi. Unsur-unsur etnomatematika dalam ragam motif batik mlatiharjan adalah objek penelitian ini. Ibu Kusmidarmini, pemilik sentra batik, adalah subjek penelitian ini. Ekplorasi, observasi, wawancara, dan dokumentasi merupakan bagian dari metode pengumpulan data. Tujuan studi batik mlatiharjan untuk mengetahui nilai matematis dan filosofis pada motif batik mlatiharjan. Hasilnya menunjukkan bahwa setiap motif memiliki makna filosofis dan konsep matematis geometri bangun datar. Motif-motif seperti Motif Bunga Jambu, Bledeg Masjid Sidomukti, Piring Champa, Masjid Agung Demak, Jambu Merah, Pohon Jambu, Jambu Belimbing, Karang Ikan, Mahkota Demak, dan Motif Sidomukti Jambu Bulus. Geometri termasuk konsep struktur datar seperti lingkaran, persegi panjang, segitiga, belah ketupat, dan trapesium dalam berbagai macam motif batik dari mlatiharjan demak.